2019
DOI: 10.3390/ma12152400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deep Cryogenic Treatment on Microstructure and Wear Resistance of LC3530 Fe-Based Laser Cladding Coating

Abstract: The effect of deep cryogenic treatment on microstructure and wear resistance of LC3530 Fe-based powder laser cladding coating was investigated in this paper. The cladding coating was subjected to deep cryogenic treatment for the different holding times of 3, 6, 9, 12, and 24 h, followed by tempering at room temperature. Microstructure of the cladding coating was observed by optical microscope (OM) and the microhardness was measured by the Vickers-hardness tester. The wear was tested by ball and flat surface gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…They also demonstrated that the low cost of Fe-based amorphous alloys is an advantage [35]. Zhang et al demonstrated that deep cryogenic treatment, applied after laser cladding Fe-based coatings, can significantly enhance the microhardness and wear resistance of such coatings [36].An original technique of laser surface melting of non-ferrous alloys in liquid nitrogen was elaborated and demonstrated by and Cui et al [40]. All these researchers point to the benefits of accelerated cooling and solidification rates due to liquid nitrogen-assisted cooling, which results in refinement of the microstructure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They also demonstrated that the low cost of Fe-based amorphous alloys is an advantage [35]. Zhang et al demonstrated that deep cryogenic treatment, applied after laser cladding Fe-based coatings, can significantly enhance the microhardness and wear resistance of such coatings [36].An original technique of laser surface melting of non-ferrous alloys in liquid nitrogen was elaborated and demonstrated by and Cui et al [40]. All these researchers point to the benefits of accelerated cooling and solidification rates due to liquid nitrogen-assisted cooling, which results in refinement of the microstructure.…”
mentioning
confidence: 99%
“…They also demonstrated that the low cost of Fe-based amorphous alloys is an advantage [35]. Zhang et al demonstrated that deep cryogenic treatment, applied after laser cladding Fe-based coatings, can significantly enhance the microhardness and wear resistance of such coatings [36].…”
mentioning
confidence: 99%
“…Besides, the crystallographic image is also shown in the Supporting Information (Supporting Information Figure S3–S5). The data show that the three molecules have well‐arranged layer‐by‐layer structures in a specific direction, which is expected to facilitate the diffusion of ions during the charge‐discharge process [21] . The interplanar distance is tested by simulated lattice information and shows that the interplanar space of TT, PT and PX is 0.70 nm, 0.72 nm and 1.01 nm (Supporting Information Figure S6), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid nitrogen bath providing cryogenic conditions of cooling was also tested by some researchers during laser surface melting or heat treatment, mainly for nonferrous alloys [18][19][20][21][22][23]. Such technique of liquid nitrogen bath cooling of the substrate was adopted and developed by the authors for laser powder deposition of metallic and composite coatings, as demonstrated in several previous publications [1,[24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%